Analysis of the Management of Village Fund Allocation in the Health Program in Tuntungan II Village, Deli Serdang Regency - Sari, Anggi Novita; Dahlan, Ulfiyah Az-Zahra; Ainy K., Nabilla Tawaqal; Ritonga, Putri Alvia; Hasibuan, Indah Doanita (Universitas Ibn Khaldun Bogor, 2024)
One of the problems of health development that occurs in the villages of Deli Serdang Regency is the high level of community diversity, which results in the complexity of the problems that arise. To complete development, especially in Tuntungan II Village, larsger funds are needed. Based on the information above, the researcher is interested in conducting further research on